Effect of Alkali Refining on Removal of Aflatoxins in Groundnut Oil and Quality Evaluation - A. Yassin1, Atif A.; . Magzoub, Reem 1; . Abdelrahman2, ; Nada; M. Abdel-, Awad (Gezira Journal of Engineering and Applied Sciences, 2019)
The present study was investigated the effect of alkali refining on the removal of aflatoxins (AFs) in groundnut oil. Groundnut oil samples were collected from different expellers in Medani and Khartoum cities in Sudan. The samples were investigated for their fungal growth using potato dextrose agar (PDA) media and quantitation of the toxins was accomplished by the thin layer chromatography (TLC) technique. The results show that most of the oil samples were affected by A. flavus and other fungi as well as contaminated with AFs. The findings show that the alkali refining processes of the groundnut oil slightly effect on the removal of AFs in groundnut oil. In addition, there was signiﬁcant difference in the physicochemical properties of the groundnut oil after treatment via alkali refining, these include the moisture content, peroxide value, acid value as well as the free fatty acids. On the other hand, there were no significant changes in the refractive index before and after alkali refining.